Poor justice: how the poor fare in the courts - Lens, Vicki (Oxford University Press, 2016)
The rule of engagement -- Welfare fair hearings -- Child maltreatment proceedings -- The justice of street level justice -- Courts as a catalyst for social change -- Protecting or coercing persons with mental disabilities -- Legal advocacy for the homeless -- The justice of social reform litigation -- The Supreme Court -- Race, education and the constitution -- Criminal justice and racial profiling -- The high justice of the Supreme Court